To Go Where Nature Leads: Focus on Palmitoylethanolamide and Related ALIAmides As Innovative Approach to Neuroinflammatory and Pain-Related Disease States in Honor of Doctor Francesco Della Valle - Cuzzocrea, Salvatore; Crupi, Rosalia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The primary compound at the core of ALIAmides, known as palmitoyl ethanolamide (PEA), has been recognized as a nutritional substance with protective qualities since the 1950s. Over time, PEA has been identified in a range of plant and animal food sources, and its role in promoting the resolution of inflammation within the mammalian body has been subject to growing scrutiny. The revelation of the intricate connection between ALIAmides and the endocannabinoid system has significantly bolstered research endeavors in this area. PEA's capacity to impact multiple targets and employ highly effective mechanisms to support homeostasis represents a substantial departure from the conventional pharmacological perspective, which often revolves around the concept of "one drug, one target, one disease." This marks the commencement of a new era in the field of human and animal health management, where a nature-aligned approach is adopted to modulate the body's responses to diverse stimuli and injuries.